Analisis Resiko Infeksi Jamur pada Wanita Hijab dan Non-Hijab Akibat Kelembapan Rambut - Erika Dwi Susanti; Azzahra Nabilla Atha; Erlanda Islami Pasha; Elsa Trisna Sari; Azizah Zahra Nur Fitria; Nur Aini Fatna Fadilla; Liss Dyah Dewi Arini (Lembaga Pengembangan Kinerja Dosen, 2026)
Hair and scalp health is an important aspect of dermatology that is influenced by various environmental and physiological factors, as well as daily habits. One factor that is often considered is the moisture level of the scalp, which can create a distinct microecological environment conducive to the growth of microorganisms. This study employed a quantitative approach with a comparative observational analytical design to analyze the relationship between hair moisture levels and the risk of fungal infection by the genus Malassezia sp. in two groups: women who wear the hijab and women who do not. The study was conducted in May 2026 in Surakarta, Solo, after obtaining informed consent from the participants. Based on macroscopic observations on PDA medium, differences in fungal colony growth were observed in each group, both in the hijab and non-hijab samples. Some samples showed more visible colony growth, while others showed only slight growth or no dominant colonies. These differences indicate that the number of microorganisms in each sample was not the same. Microscopic observations using LPCB staining revealed fungal structures consisting of round cells in several preparations. This study suggests that wearing a hijab can increase scalp temperature and humidity, potentially supporting the growth of Malassezia sp. However, the results of both macroscopic and microscopic cultures indicate that fungal growth varies among individuals and is not necessarily higher among hijab wearers.